The Demand-Side Story: Structural Change and the Decline in Female Labour Force Participation in India - Ashwini Deshpande; Jitendra Singh (Institute of Labor Economics (IZA), 2024)
Mainstream literature attributes the decline in female labour force participation rate (FLFPR) in India between 2004-05 and 2017-18 primarily to supply-side factors. In this paper, we show that, in fact, demand-side factors are predominantly responsible for the decline. We begin by demonstrating that the contribution of supply-side factors to the FLFPR decline has been reducing over time. Changes in supply-side factors explain a miniscule part of the decline between 2011-12 and 2017-18. We estimate the contribution of structural transformation and local labour demand as the key determinants of declining FLFPR. Our identification strategy uses the Bartik shift-share instrument as the instrumental variable for measuring exogenous change in local labour demand. We find that female employment is highly responsive to local labour demand, but not male employment. The period of decline in FLFPR has also been a period of "jobless growth". We show that women have borne the brunt of the stagnant employment creation from 2004-05 onwards. Our analysis suggests that India needs to focus on creating rural non-farm jobs to boost FLFPR.
Keywords: J23; J71; J16; O53; 330; female labour force participation rate; employment; social norms; India; labour demand